The Effect of Probiotic Feeding with Different Dosages on the Growth of Barramundi (Lates Calcarifer) Using a Recirculation System - Dwi Wahyuni; Iskandar Putra; Niken Ayu Pamukas (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Barramundi ( lates calcarifer ) is a fish that has important economic value as a consumption fish. The amount of feed spent in the cultivation of Barramundi is high enough. Addition of probiotics to feed is one of efforts made to be able to streamline the amount of feed in the maintenance of Barramundi. The purpose of this study was to analyze the effect of probiotic addition on the growth of Barramundi use system recirculation as well as got dose the best probiotics. This research implemented on 24 July 2021 – 01 September 2021 for 40 days at the Gogok Marine Aquaculture Center (BPBL), Kepulauan Meranti Regency, Riau Province. Method used in this study Completely Randomized Design (CRD) with 5 treatment levels and 3 replications. Treatment in study this is giving Probiotic probio-7 with different dosage namely P0 ( Control ), P1 (10 mL/kg feed ), P2 (20 mL/kg feed ), P3 (30 mL/kg feed ), and P4 (40 mL/kg feed ). Results research that has been done could known that addition probiotics on feed take effect to growth Barramundi (L. calcarifer). Treatment best obtained on treatment dose probiotics 20 ml/kg feed with weight absolute 13.84 grams, length absolute 2.16 cm, speed growth 3.50% specific , efficiency feed 61.43%, and conversion feed 1.62%.